Tales of subversion : queering knowledge, female experience and patriarchy in Carmen Maria Machado’s literary landscape - Van der Walt, Khenje Demee (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2025.